In Situ Study of Hydrogen Accumulation in the E110 Zirconium Alloy during Gas-Phase Hydrogenation by the Methods of Thermal Desorption Spectroscopy and Synchrotron X-Ray Diffraction Analysis; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 17, Sup. 1 - Kruglyakov M. A. Mark Aleksandrovich; Laptev R. S. Roman Sergeevich; Syrtanov M. S. Maksim Sergeevich; Kudiyarov V. N. Victor Nikolaevich (2023, 2023)
Title screen